Al-MOF-derived spindle-like hierarchical porous activated carbon for advanced supercapacitors. Issue 6 (25th January 2022) - Liu, Xingyu; Wang, Xiaoyue; Miao, Rui; Sun, Yanzhi; Chen, Yongmei; Tang, Yang; Wan, Pingyu; Pan, Junqing
Abstract : Spindle-like hierarchical porous activated carbon materials derived from Al-BTEC possess high specific capacitance and good cycling stability. Abstract : Metal organic frameworks (MOFs) and their derivatives have been widely used in electrochemistry due to their adjustable pore size and high specific surface area (SSA). Herein, a spindle-like hierarchical porous activated carbon (SPC) was synthesized through carbonizing the Al-BTEC precursor and then alkaline washing with NaOH. The fabricated SPC has a uniform shuttle-shaped structure, showing a large BET surface area of 1895 m 2 g −1 and an average pore size of 2.4 nm. The SPC product displays a high specific capacitance (SC) of 337 F g −1 at 1 mV s −1 and 334 F g −1 at 1 A g −1 . The retention of SC is about 95% after 100 000 cycles when the current density is 50 A g −1, indicating its excellent stability. Furthermore, the assembled symmetrical capacitor with a two-electrode system exhibits a high SC of 173 F g −1 at 1 A g −1 and an energy density of 15.3 W h kg −1 at a power density of 336 W kg −1 . This work would provide a new pathway to design and synthesize carbon materials for supercapacitors with excellent properties in the future.